The Response of International Higher Education Associations to COVID-19 - Blanco, Gerardo; de Wit, Hans (International Higher Education, 2020)
COVID-19 impacts not only students and staff at colleges and universities, but also academic associations, including international higher education associations, forcing them to adapt how they provide support and expertise to their members.